Brown Bowel Syndrome Presenting as a Small Bowel Obstruction. Issue 6 (November 2018) - Alwatari, Yahya; Preciado, Christopher; Tondon, Rashmi; Shiroff, Adam
Abstract : Abstract: Brown bowel syndrome (BBS) is a rare condition characterized by lipofuscin deposition in the muscularis propria of the bowel. It is associated with vitamin E deficiency and malabsorptive syndromes. We report a case of BBS in a patient with previously undiagnosed primary intestinal lymphangiectasia. The patient had a longstanding history of malnutrition as well as bilateral lower extremity lymphedema and chylous ascites. He presented to our hospital with small bowel obstruction (SBO). Initial magnetic resonance enterography revealed a dilated duodenum, which when biopsied revealed only lymphangiectasia and lymphedema. He was managed conservatively and discharged following resolution of the obstruction. The patient presented again 1 month later with SBO that failed to resolve with conservative treatment. Subsequent exploratory laparotomy discovered a portion of pale, edematous, aperistaltic jejunum. The specimen was resected, and pathologic examination revealed brown granular pigment deposition within the muscularis propria, which was highlighted by periodic acid–Schiff and lipofuscin stains, diagnostic of BBS. Nutritional workup revealed multiple deficiencies. The patient's clinical findings and history were suggestive of primary intestinal lymphangiectasia with resulting nutritional deficiencies leading to BBS. Outpatient follow-up after recovery revealed an elevated 24-hour fecal α1 antitrypsin, which supports this diagnosis. The patient has since improved following adherence to a low-fat diet. The combined clinical, radiographic, and pathologic findings in this case allowed for the resolution of this complex diagnostic dilemma. Although rare, BBS remains an important consideration in the differential diagnosis of a patient with SBO and history of chylous ascites and should be viewed as a symptom of underlying treatable nutritional deficiency.